DIGITAL GLOBALIZATION AND THE TRANSFORMATION OF ISLAMIC EDUCATION: CHALLENGES, OPPORTUNITIES, AND CHARACTER STRATEGIES - Azzahra Iswi Marita; Asna Asna; Siti Julaiha (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to identify strategic issues in Islamic education related to digital globalization and to analyze the challenges, opportunities, and character-strengthening strategies that can be implemented in the modern era. The method used is a literature review with a systematic approach following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The literature selection process was conducted using the Publish or Perish application with the keywords “Digital Globalization,” “Islamic Education,” and “Character Strengthening.” From 100 collected articles, 50 were screened, and finally, 10 main journals were identified as highly relevant for in-depth analysis. The findings indicate that digital globalization presents serious challenges to Islamic education, including a moral crisis among the younger generation, the overwhelming flow of information that may cause distortion in religious understanding, and the growing dependence on technology that could weaken the role of teachers and Islamic educational institutions as moral exemplars. However, digital globalization also provides significant opportunities such as the development of interactive learning models, technology-based da’wah access, and efficiency in Islamic education management. Character-strengthening strategies are crucial to address these dynamics. Integrating moral, spiritual, and digital literacy values into the curriculum, utilizing technology in a guided manner, and fostering synergy among families, schools, and communities are strategic steps in shaping a generation of Muslims who are adaptive, critical, and possess noble character. Thus, digital globalization can serve as a momentum for transforming Islamic education toward a more modern, relevant, and character-oriented system.